2021
DOI: 10.1016/j.nicl.2021.102731
|View full text |Cite
|
Sign up to set email alerts
|

Same salience, different consequences: Disturbed inter-network connectivity during a social oddball paradigm in major depressive disorder

Abstract: Highlights No significant difference in BOLD responses in the SN between controls and patients. Anhedonic symptomatology relates to diminished BOLD signals in the left amygdala. Enhanced functional connectivity from the SN to the DMN in depression. Reduced functional connectivity from the SN to the VAN in depression. Altered processing in depression is coded in disturbed inter-network connectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…49 For example, patients with depression show increased connectivity in the DMN. 50,51 FNC was significantly decreased in the prefrontal region of the DMN and increased in the hippocampus in glioma patients, which was associated with tumor grade. 52 The results of our study indicate that the left MSFG (extending to the right MSFG) of the DMN was lower in the DON group than in HCs, suggesting that decreased FNC in the DMN is related to dysfunctional emotional cognition in DON.…”
Section: Intra-and Internetwork Comparisons Of Fncmentioning
confidence: 90%
See 1 more Smart Citation
“…49 For example, patients with depression show increased connectivity in the DMN. 50,51 FNC was significantly decreased in the prefrontal region of the DMN and increased in the hippocampus in glioma patients, which was associated with tumor grade. 52 The results of our study indicate that the left MSFG (extending to the right MSFG) of the DMN was lower in the DON group than in HCs, suggesting that decreased FNC in the DMN is related to dysfunctional emotional cognition in DON.…”
Section: Intra-and Internetwork Comparisons Of Fncmentioning
confidence: 90%
“…Altered connectivity in the DMN have been linked to mental disorders 49 . For example, patients with depression show increased connectivity in the DMN 50,51 . FNC was significantly decreased in the prefrontal region of the DMN and increased in the hippocampus in glioma patients, which was associated with tumor grade 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis showed that the structural connectivity between the left anterior cingulate gyrus and the left orbital gyrus in DMN increased with the severity of the disease. As the synergy of the left cingulate gyrus increased, multiple areas of the network were damaged, and the overall network was eventually affected [19]. In ECN, the connectivity between the left anterior cingulate gyrus and the right orbital gyrus increased with the severity of the disease, and gradually spread the damage to the frontal lobe [16].…”
Section: Discussionmentioning
confidence: 99%
“…In task-positive systems, the default mode network (DMN) [13][14][15] and the executive control network (ECN) [16,17] are two major networks closely related to depression, and the default network has always been considered to be related to the severity of MDD at rest [18]. DMN is one of the most prestigious brain networks and mainly includes the frontal lobe, cingulate gyrus and parietal lobe [19]. ECN mainly includes the lateral prefrontal cortex, cingulate gyrus and posterior parietal cortex [16].…”
Section: Introductionmentioning
confidence: 99%